Giant Cell Reparative Granuloma of the Orbit: Clinicopathological Characteristics and Treatment - Álvaro Bengoa-González; Enrique Mencía-Gutiérrez; Beatriz Alonso-Martín; Bianca-Maria Laslău; Elena Salvador; Ana-Belén Enguita-Valls; María-Dolores Lago-Llinás (Case Reports in Ophthalmological Medicine)
Giant cell reparative granuloma (GCRG) is a rare fibroosseous lesion uncommonly seen in the orbital area. Although benign, it is known to be recurrent and locally destructive. We report two cases of GCRG of the orbit. In both cases, computed tomography revealed a heterogeneously growing well-defined mass, arising from the roof of the orbit, affecting the cortex, and invading the orbit. In the first case, the mass extended into the anterior cranial fossa. Magnetic resonance imaging with gadolinium showed, in both cases, a cystic character of the lesion with fluid levels. The surgical treatment was performed via an upper crease incision. An ultrasonic aspirator system was used to remove the tumor tissue and its extension into cranial fossa. Careful histopathologic analysis established the diagnosis of GCRG. Symptoms resolved completely with no evidence of recurrence after a follow-up of 18 and 14 months, respectively. We present the clinicopathological and radiological findings, and we describe the surgical approach. As a rare entity, GCRG of the orbit should be considered in differential diagnosis of fibroosseous orbital masses. Complete surgical excision carries a low risk of recurrence.